Optimization of Tax Education Through Digital Content - Ardi Wijaya; Maskuri Sutomo (IJESS International Journal of Education and Social Science, 2023)
Tax education is important for the public, especially for taxpayers, in order to understand their rights and obligations in paying taxes. However, tax education still does not receive adequate attention in Indonesia. Digital content as a medium for tax education offers easier access and greater flexibility for students. This research aims to review the effectiveness and challenges in optimizing tax education through digital content. The research method used in this research is a literature study analysis method to review various studies related to the effectiveness and challenges in optimizing tax education through digital content. Data is collected from academic journals, books, reports and other related articles. The results of this research reveal that digital content as a tax education medium can improve tax understanding and skills. Digital content allows digital actors to learn independently and flexibly, as well as allowing access to various learning resources, and providing more interesting and interactive interactions.